2022
DOI: 10.3389/fcell.2022.824075
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Endometrial Cell-Derived Exosomal Moesin Induces Eutopic Endometrial Cell Migration, Enhances Angiogenesis and Cytosolic Inflammation in Lesions Contributes to Endometriosis Progression

Abstract: Background: Endometriosis (EMs) is the most common gynaecological disorder with its etiology and/or pathophysiology remains enigmatic. Recent studies showed that extracellular vesicles (EVs), exosomes in particular, play a critical role in developing various clinical disorders. However, the implication of exosomes in endometriosis progression has not been well elucidated.Method: The ectopic stromal cellular exosomes (eEVs) were assessed by transwell assay, scratch tests, tube formation assay, western blot, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This process mediates the exchange of information between cells. In the context of EMs, ESCs, macrophages, and mesenchymal stem cells (MSCs) engage in communication through EVs that carry specific substances (36)(37)(38). These EVs mediate various signaling pathways, ultimately promoting the progression of EMs.…”
Section: Evs Are Involved In Mediating Emsmentioning
confidence: 99%
See 2 more Smart Citations
“…This process mediates the exchange of information between cells. In the context of EMs, ESCs, macrophages, and mesenchymal stem cells (MSCs) engage in communication through EVs that carry specific substances (36)(37)(38). These EVs mediate various signaling pathways, ultimately promoting the progression of EMs.…”
Section: Evs Are Involved In Mediating Emsmentioning
confidence: 99%
“…ESCs play a key role in the development of EMs by releasing EVs containing specific substances that stimulate surrounding ESCs and other recipient cells, thereby promoting angiogenesis, fibrosis, and mediating EMs. For example, Abudula et al found that EVs derived from ESCs induced normal endometrial stromal cell migration, angiogenesis, and upregulation of inflammatory cytokine expression in ovarian cells (36). Li et al found that EVs derived from ectopic ESCs (eESCs) promote lymphangiogenesis (39).…”
Section: Evs Are Involved In Mediating Emsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blocking of EVs reduces pro-neuro angiogenesis induced by EVs, indicating that EVs play an important role in neuro-angiogenesis in EMs [ 53 ]. Qiu et al demonstrated that enriched lncRNA aHIF from ESCs-derived EVs can facilitate the angiogenesis of EMs by activating vascular endothelial growth factor (VEGF)-A, VEGF-D and basic fibroblast growth factor [ 42 , 54 , 55 ]. In addition, the expression of miR-15a-5p in EVs from ovarian ectopic endometrium was downregulated [ 43 ].…”
Section: Abnormal Levels Of Evs In Emsmentioning
confidence: 99%